Bongkrekic acid poisoning: Severe liver function damage combined with multiple organ failure caused by eating spoiled food. (November 2019) - Shi, Ruijuan; Long, Chaoyang; Dai, Yunda; Huang, Qiong; Gao, Yuzhen; Zhang, Nengpei; Chen, Yanchang; Liu, Shuiping; Ma, Qianqian; Quan, Li; Zhang, Yonghui; Luo, Bin
Highlights: We report 5 relatively rare reported cases of bongkrekic acid-induced food poisoning. The forensic pathological features and clinical manifestations of the poisoning were described in detail. LC-MS/MS was used to detect victims' serums and suspected foods containing toxic substances. The results showed that certain concentrations of bongkrekic acid were detected. We found that the difference in blood glucose between the deceased and survivors of the five victims may be an indication of the severity of the disease. Comparing bongkrekic acid poisoning with other diseases which can also cause severe liver damage and multiple organ failure, several characteristics are summarized for forensic identification and early clinical diagnosis and treatment. Abstract: Bongkrekic acid (BA) poisoning can be caused by eating spoiled or fermented foods contaminated with pseudomonas cocovenenans. Although some in vitro studies have been reported on the use of purified BA to interfere with cell metabolism, few clinical or pathological data of BA poisoning on human due to food-borne factors are available for forensic appraisal. For the first time, we retrospectively report five cases of food-borne poisoning caused by eating rice noodles, a popular traditional food in Guangdong, China, and three of the victims died. All five victims were hospitalized with gastrointestinal symptoms such as nausea, vomiting and diarrhea and were treated with admission diagnosis of liver failure and acute kidney damage. Certain concentrations of BA were detected in the victims' peripheral blood serums at the hospitalization (ranging from 70–345 μg/L) and the suspected poisonous foods (0–810 ng/g) with LC-MS/MS technique. The results of forensic pathological examination showed that all three deceased had severe liver and kidney damage, accompanied by multiple organ congestion and edema, which were consistent with clinical diagnosis. Combined with the clinical records, we found that the difference in blood glucose between the deceased and survivors of the five victims may be an indication of the severity of the disease. In addition, we compared BA poisoning with other diseases that can cause acute liver function damage in terms of pathological characteristics and clinical manifestations, which has important reference significance for the diagnosis and forensic appraisal of this food-borne poisoning.